Green Loans and Bank Intermediary Costs: : Evidence from Net Interest Margin and Loan Interest in Indonesia - Tumbelaka, Indra; Handogo, Heru Setyo (The International Journal of Financial Systems, 2026)
Employing a unique dataset of green and non-green loans in Indonesia, we show that banks’ loan allocation in environmentally and non-environmentally friendly activities are associated with bank intermediary costs. Our study utilizes green loan taxonomies released by the Indonesian Financial Services Authority to classify loans into green, transition, and unqualified categories. Using dynamic and static models, as well as GMM and fixed-effects estimators on bank-level panel data, we provide evidence that banks with larger green loan portfolios have lower intermediation costs, whereas banks with larger non-green loan portfolios have higher intermediation costs. We further confirm our findings by showing that green loans are associated with lower bank and loan interest spreads, implying that banks in a developing country consider environmental information in their lending decisions and perceive green loans as less risky. Our study contributes to the literature on net interest margins and green loan pricing in developing countries.